The effect of hypoxia on free and encapsulated adult porcine islets—an in vitro study. (5th November 2016) - Muthyala, Sudhakar; Safley, Susan; Gordan, Kereen; Barber, Graham; Weber, Collin; Sambanis, Athanassios
Abstract: Background: Adult porcine islets (APIs) constitute a promising alternative to human islets in treating type 1 diabetes. The intrahepatic site has been used in preclinical primate studies of API xenografts; however, an estimated two‐thirds of donor islets are destroyed after intraportal infusion due to a number of factors, including the instant blood‐mediated inflammatory reaction (IBMIR), immunosuppressant toxicity, and poor reestablishment of extracellular matrix connections. Intraperitoneal (ip) transplantation of non‐vascularized encapsulated islets offers several advantages over intrahepatic transplantation of free islets, including avoidance of IBMIR, immunoprotection, accommodation of a larger graft volume, and reduced risk of hemorrhage. However, there exists evidence that the peritoneal site is hypoxic, which likely impedes islet function. Methods: We tested the effect of hypoxia (2%‐5% oxygen or pO2 : 15.2‐38.0 mm Hg) on free and encapsulated APIs over a period of 6 days in culture. Free and encapsulated APIs under normoxia served as controls. Islet viability was evaluated with a viability/cytotoxicity assay using calcein AM and ethidium bromide on days 1, 3, and 6 of culture. Alamar blue assay was used to measure the metabolic activity on days 1 and 6. Insulin in spent medium was assayed by ELISA on days 1 and 6. Results: Viability staining indicated that free islet clusters lost their integrity and underwent severe necrosis under hypoxia; encapsulated islets remained intact, even when they began to undergo necrosis. Under hypoxia, the metabolic activity and insulin secretion (normalized to metabolic activity) of both free and encapsulated islets decreased relative to islets cultured under normoxic conditions. Conclusions: Hypoxia (2%‐5% oxygen or pO2 : 15.2‐38.0 mm Hg) affects the viability, metabolic activity, and insulin secretion of both free and encapsulated APIs over a six‐day culture period. Encapsulation augments islet integrity under hypoxia, but it does not prevent loss of viability, metabolic activity, or insulin secretion.